Does preoperative platelet count and thrombocytosis play a prognostic role in patients undergoing nephrectomy for renal cell carcinoma?: Results of a comprehensive retrospective series - Brookman‐May, Sabine D.; May, Matthias; Ficarra, Vincenzo; Kainz, Manuela Christine; Kampel-Kettner, Karin; Kohlschreiber, Stephanie; Wenzl, Valentina; Schneider, Meike; Burger, Maximilian; Wieland, Wolf F.; Otto, Wolfgang; Tilki, Derya; et al. (World journal of urology, 2013)
To evaluate the still controversially discussed prognostic role of preoperative platelet level (PPL) and thrombocytosis (TC) in patients who undergo surgery for renal cell carcinoma (RCC) based on the largest patient series reported to date.
Published online: 19 August 2012
Gesehen am 08.12.2020